2022
DOI: 10.37771/nj.vol6.iss2.836
|View full text |Cite
|
Sign up to set email alerts
|

Kualitas Tidur Dan Indeks Massa Tubuh Pada Remaja

Abstract: Abstrak Body Mass Index (BMI) is a simple anthropometric index to monitor nutritional status, especially about bodywight. Weight gain is often associated with poor sleep quality due to hormonal regulation in the hypothalamus, which causes an increase in amount of fat tissue which leads to obesity. The purpose of this study was to determine the relationship between quality of sleep and body mass index in Vox-Dei GMIM Zaitun Mahakeret adolescents. Descriptive correlation with a cross-sectional approach was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…The incidence of overnutrition and an increase in body mass index is closely related to poor sleep quality in adolescents. Sleep quality includes sleep duration, frequency of awakenings, and subjective assessment of one's sleep satisfaction (Pitoy et al, 2022). Woran et al (2020) reported that 72.5% of high school youth in North Sulawesi had poor sleep quality due to activities at night, such as doing assignments and playing with gadgets.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of overnutrition and an increase in body mass index is closely related to poor sleep quality in adolescents. Sleep quality includes sleep duration, frequency of awakenings, and subjective assessment of one's sleep satisfaction (Pitoy et al, 2022). Woran et al (2020) reported that 72.5% of high school youth in North Sulawesi had poor sleep quality due to activities at night, such as doing assignments and playing with gadgets.…”
Section: Introductionmentioning
confidence: 99%
“…Akibat dari kualitas tidur buruk, seseorang dapat merasa tidak segar di pagi hari, rasa lelah, suasana hati buruk, merasa sakit kepala di pagi hari, disfungsi kegiatan di siang hari, rasa mengantuk, konsentrasi yang buruk, serta rasa sakit dan nyeri di siang hari (Libman, et al, 2016). Kualitas tidur yang buruk dapat menyebabkan kenaikan berat badan dikarenakan adanya regulasi hormon di hipotalamus sehingga menyebabkan meningkatnya jumlah jaringan lemak dalam tubuh yang mengarah pada kejadian obesitas (Pitoy, et al, 2022). Salah satu cara untuk menentukan berat badan seseorang dalam kategori kurus, normal atau obesitas menggunakan Indeks Massa Tubuh (IMT).…”
unclassified